La sexualité, la métaphore et la différence des cultures : à l’exemple de „La Curée” d’Émile Zola et sa traduction polonaise - Kaczmarek, Anna (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
In the literature of the 19th century, sexuality may be painted only in an indirect way, through allusions or metaphors. In Émile Zola’s La Curée, plants in a greenhouse express and symbolize the character’s desire. However, the force of the original image is completely lost in the Polish translation, made in the 1950s. Being a product of the Communist period, this text doesn’t take into consideration the cultural aspect of the process of translation. An attempt to imitate the lexical and syntactic structure is made at the cost of pictorial description, characteristic of Zola’s prose. Therefore, the most beautiful fragments of French novel remain nearly unknown to polish readers.